Strategi Pengembangan Pariwisata di Kabupaten Ngawi, Jawa Timur - Nurul Amsori; Yusuf Adam Hilman; Bambang Widiyahseno; Irvan Nur Ridho (Lasigo Akademia Indonesia, 2022)
The tourism development strategies are important to support the existence of tourism in the future which is one of the supporting sectors of the economy. In Ngawi Regency, East Java Povince, the tourism development strategy is carried out by the Ngawi Regency Tourism, Youth and Sports Office. This institution was formed to support the Ngawi Regency government in the fields of tourism, youth and sports. This research was conducted to find out the tourism development strategy in Ngawi Regency and the obstacles and supporting factors in the process of implementing the tourism development strategy in Ngawi Regency by the Ngawi Regency Tourism, Youth and Sports Office. This research is a qualitative descriptive. Data were collected through interviews, observation and document study. Informants were selected purpsosively. Tringulation has employed for data validation. Data analysis is carried out through the process of data reduction, data presentation, and data conclusions. The results show that the tourism development strategy in Ngawi Regency is carried out through brandin/promotion, human resource development, and inprovemnet and management of the tourism facility and infrastructure. In addition, there are factors supporting the development of Ngawi tourism, namely the quality and quantity of sufficient employees, the existence of many events, the support from other parties, and sufficient funds. Meanwhile, the existence of tourism in other areas is a challenge in developing Ngawi tourism.